Effectiveness of Betel Leaf Extract (Piper betle, Linn) as Anopheles spp Mosquito Repellent - Khomsatun Khomsatun; Arif Widyanto; Susiyanti Susiyanti (Poltekkes Kemenkes Semarang, 2013)
The method used is an experiment in a laboratory. Anopheles sp obtained from eggs. Betel leaf extract concentration of 20%, 40% and 80% tested thrust or power protection against Anopheles spp. Observations on the number of mosquitoes that landed on the arm of every hour starting at 1st (immediately after the application of) up to 6th hour. Power protection betel leaf extract is effective if ≥ 90% power protection.The results showed that the protective power of betel leaf extract against Anopheles spp at a concentration of 20% by 50%, the concentration of 40% as much as 68.75% and a concentration of 80% as much as 93.75%. Power protection is effective concentrations of 80% with 93.75% of power protection. This is consistent with the Commission on Pesticides (1995, H.2) which states that the repellent is considered effective if ≥ 90% power protection.